(untitled) (Palíndromo, 2025)
This article discusses the reception and art criticism of exhibitions featuring the works of Arthur Bispo do Rosário, analyzing a general overview of the discussions his works provoked in the art field in the 1990s. Specifically, it focuses on reviews of the exhibition of Bispo’s works as one of the brazilian representatives at the 46th Venice Biennale in 1995; the exhibition "Eu preciso destas palavras. Escrita" held at Caixa Cultural in 1999; and the group exhibition "Por que Duchamp? Leituras duchampianas por artistas e críticos brasileiros." in 1999 at Itaú Cultural in São Paulo. Based on an analysis of newspaper art critics, curatorial texts, and exhibition catalogs, this article aims to map and discuss attempts to legitimize Bispo as a contemporary artist and the comparisons and parallels between his life and work and those of major names in national and international art. It was found that the debates surrounding the presence of Bispo do Rosário’s works in the exhibition circuit involve complex issues for critics, such as the definition of art, the boundaries between sanity and madness, the appropriation of objects without artistic intention, and his categorization as an artist. Art scholars seek to validate him through comparisons with other artists and the aesthetic, political, and poetic value of his works. This article analyzes specific critical texts to illustrate these discussions and highlight the lasting impact of Bispo do Rosário’s work, particularly since the 1990s.